Prospects for Creating an Interregional Innovation Center in the Russian Far East - SAVALEY, Viktor Vasilevich (Journal of Advanced Research in Law and Economics, 2017)
The research proposes a classification of the organizational forms of objects of innovative infrastructure in Russia and analyzes their distribution by regions (federal districts). It is concluded that despite the diversity of forms of organizing the innovation activity, the degree of penetration of the innovations into the production process remains low. The rating estimates of the investment activity by regions are given. Based on the results of the processing of statistical reports, the status of the innovation activity of the enterprises in the Far East of Russia is characterized in comparison with the average values for the country, making it possible to assess the level of the innovative demand in the economy of the region. The immanent objective factors, limiting the expansion of the innovative demand in the economy of the Russian Far East, are revealed. At the same time, the existence of favorable conditions is demonstrated, including the economic and administrative preferences for investors and resellers, for the purposes of creation of the priority innovative development area within the boundaries of the Vladivostok agglomeration. One of the key components of this project should be an interregional innovation center capable of becoming a generator of the innovations and their spread in this region.